Governing Internet Territory: ICANN, Sovereignty Claims, Property Rights and Country Code Top-level Domains - Mueller, Milton L.; Badiei, Farzaneh (Science and Technology Law Review, 2017)
This paper examines the legal and Internet governance controversies over country code top-level domain names (ccTLDs). In recent litigation (Weinstein v. Islamic Republic of Iran and ICANN), terrorism victims argued that ccTLDs are property and attempted to seize Iran’s .IR domain for compensation. In refusing to uphold this claim, an appeals court ruled that a court-ordered redelegation would impair the Internet Corporation for Assigned Names and Numbers’ (ICANN’s) role in global Internet governance. While the .IR case is recent, the underlying tensions between state sovereignty, the role of ICANN and the rights of organizations that have been awarded ccTLDs have been simmering for two decades. Three governance models are in play: a sovereignty-based model, a property rights/market-based model, and a global public trustee model. The legal and political science literature leaves this Internet governance issue unexplored and unsettled, while court rulings on the property status of domains have been mixed or indecisive. Most legal scholars merely assume that states have sovereignty rights over their ccTLDs and do not critically assess the justification for, or the implications of, a sovereignty-based model. Likewise, many legal scholars, governments and Internet governance institutions have resisted recognizing TLD delegations as a property right, but their arguments are often based on misunderstandings of the economics and technology of the domain name system. Drawing on law, economics and sovereignty theories, this paper shows that top-level domain names have all the essential features of a property right. It argues that a governance regime that recognized them as such would be preferable to a regime based on sovereignty claims or a global public trustee model.